Logico-semantic analysis of aesthetic concepts and its implications for the ontology of aesthetic proprieties - Zahrádka, Pavel (Bohemica Olomucensia, 2015)
The paper deals in the first part with the semantic analysis and classification of aesthetic concepts. Subsequently, on the basis of this analysis three conclusions are inferred that are relevant to the ontology of aesthetic properties. Firstly, the predicate function of evaluative aesthetic concepts is refuted. Secondly, the distinction between aesthetic and non-aesthetic concepts is discussed. I argue for the thesis that this distinction is not categorical, but functional one, and therefore does not imply the introduction of a special ontological category for aesthetic properties. Thirdly, the possibility of separating the evaluative and descriptive component of mixed aesthetic concepts is discussed. I defend the thesis that mixed aesthetic concepts have the semantic structure of thick concepts. The evaluative function of aesthetic concepts proves the relational nature of aesthetic properties, on the basis of which it is necessary to reject the version of the aesthetic realism construing the existence of aesthetic qualities as independent on the perceiving subject.
Keywords: Semantic analysis; classification of aesthetic concepts; evaluative aesthetic concepts; descriptive aesthetic concepts